2012
DOI: 10.1021/jp304783z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polymer Morphology on Proton Solvation and Transport in Proton-Exchange Membranes

Abstract: The effects of polymer morphology on proton solvation and transport in hydrated Nafion are investigated by using a novel reactive molecular dynamics approach. Three of the most significant morphological models of Nafion, the lamellar model, the cylinder model, and the cluster-channel model, are studied. The three models exhibit distinct proton transport (PT) patterns, which result in different proton diffusion rates. In both the lamellar and the cylinder models, the interaction between protons and the sulfonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 100 publications
(186 reference statements)
4
67
0
Order By: Relevance
“…In this way, the significant changes in structures were not observed, testifying the negligible relationship between the direction of the cluster and the electric field. A similar approach was also used in previous work (Feng et al, 2012) to maintain the desired geometric shapes of water domains in Nafion membranes. This restraint has a negligible impact on the electroosmotic properties, which can be justified for two reasons: (i) because of the characteristic of hydrophobicity, the positions of the backbone carbon atoms are much further from the protons by comparison with the sulfonate groups; and (ii) our target system is a fuel cell in which the Nafion polymers are somehow tightened and fixed from both sides of the membrane.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, the significant changes in structures were not observed, testifying the negligible relationship between the direction of the cluster and the electric field. A similar approach was also used in previous work (Feng et al, 2012) to maintain the desired geometric shapes of water domains in Nafion membranes. This restraint has a negligible impact on the electroosmotic properties, which can be justified for two reasons: (i) because of the characteristic of hydrophobicity, the positions of the backbone carbon atoms are much further from the protons by comparison with the sulfonate groups; and (ii) our target system is a fuel cell in which the Nafion polymers are somehow tightened and fixed from both sides of the membrane.…”
Section: Computational Detailsmentioning
confidence: 99%
“…An increase in EW results in the larger sulfonate-sulfonate separation, and thus hinders proton transport through hydrophilic channels (Allahyarov and Taylor, 2011). Theoretical and computational analyses, such as molecular dynamics (MD) simulations and ab initio simulations, have been used extensively to investigate proton transport properties including electroosmosis in Nafion membranes and thin films (Feng et al, 2012, Feng and Voth, 2011, Jorn et al, 2012, Petersen and Voth, 2006, Petersen et al, 2005, Tse et al, 2013, Seeliger et al, 2005, Spohr et al, 2002, Cui et al, 2007, Jang et al, 2004, Wang et al, 2011a, Karo et al, 2010, Knox and Voth, 2010, Komarov et al, 2013, Spohr, 2007, Mabuchi and Tokumasu, 2014, Wescott et al, 2006, Tuckerman et al, 1995, Eikerling et al, 2008, Kornyshev and Spohr, 2009, Choe et al, 2008, Yan et al, 2008, Aochi et al, 2016, Kurihara et al, 2017. However, extensive simulations using ab initio methods for a larger number of atoms, where systems reproduce nanostructured Nafion morphology and water domains with reliable statistics, have been limited because of the high computational cost of such simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies have been devoted to providing a detailed relationship between the morphological features and proton transport using both classical MD and RMD simulations . Liu et al .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Over the past years, the structures and proton transport of many types of copolymers, including perfluorocarbon and aromatic polymers, have been simulated extensively using various techniques. [9][10][11][12][13][14][15] Choe et al reported the proton dynamics in Nafion and sulfonated polyethersulfone determined from first-principles molecular dynamics (FPMD) simulations. [16][17][18] Jorn et al used the multistate empirical valence bond model to investigate the proton conductivity of Nafion using classical molecular dynamics (MD) and coarse-grained descriptions.…”
Section: Introductionmentioning
confidence: 99%